2017
DOI: 10.1002/asia.201601617
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of β‐Keto Sulfones by a Catalyst‐Free Reaction of Aryldiazonium Tetrafluoroborates, Sulfur Dioxide, and Silyl Enol Ethers

Abstract: A green approach for the generation of β-keto sulfones through a reaction of aryldiazonium tetrafluoroborates and sulfur dioxide with silyl enol ether under catalyst- and additive-free conditions has been realized. This reaction proceeds efficiently at room temperature and goes to completion in half an hour. During the reaction process, aryldiazonium tetrafluoroborate is treated with DABCO⋅(SO ) (DABCO=1,4-diazabicyclo[2.2.2]octane) to provide a sulfonyl radical as the key intermediate, which then initiates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(14 citation statements)
references
References 120 publications
0
14
0
Order By: Relevance
“…Significantly, the bioactive molecule 3ib was synthesized on a gram scale with a good yield (Scheme B) . In contrast, the preparation of 3ib was reported by several methods, in which only a 0.2 mmol scale reaction was performed. ,,, There are also some other unsatisfactory defects associated with these methods, such as the use of complex and expensive substrates or sulfonation reagents, the requirement of a photocatalyst or metal catalyst, which will increase the cost and the difficulty of purification, and the decrease in the efficiency of the atomic economy.…”
mentioning
confidence: 99%
“…Significantly, the bioactive molecule 3ib was synthesized on a gram scale with a good yield (Scheme B) . In contrast, the preparation of 3ib was reported by several methods, in which only a 0.2 mmol scale reaction was performed. ,,, There are also some other unsatisfactory defects associated with these methods, such as the use of complex and expensive substrates or sulfonation reagents, the requirement of a photocatalyst or metal catalyst, which will increase the cost and the difficulty of purification, and the decrease in the efficiency of the atomic economy.…”
mentioning
confidence: 99%
“…67 Using this reaction framework, Wu and co-workers demonstrated that sulfonyl radical addition to silyl enol ethers, SET to generate a carbocation, and desilylation could be used to prepare β-keto sulfones. 68…”
Section: Radical Reactionsmentioning
confidence: 99%
“…67 Using this reaction framework, Wu and co-workers demonstrated that sulfonyl radical addition to silyl enol ethers, SET to generate a carbocation, and desilylation could be used to prepare -keto sulfones. 68 Several methods have also been used to prepare -functionalized sulfones via addition of nucleophiles to cation intermediates (Scheme 23, C). 69 Intramolecular nucleophile addition can also be used to prepare cyclized products, 70 and the combination of several radical addition and cyclization steps has been used to prepare complex sulfonyl-containing molecules.…”
Section: Scheme 22 Metal-free Synthesis Of 3-sulfonated Coumarinsmentioning
confidence: 99%
“…Furthermore, the functionalization with SO2 building blocks has been achieved in various small organic molecules over time. [34][35][36][37][38][39] A selection of recent (yet arbitrarily) examples of SO2 capture and functionalization are depicted in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%